Interdsiciplinary management of co-existent mucosal fenestration and dehiscence in a maxillary central incisor with immature apex : A case report - Sweta Rastogi; Kulvinder Singh Banga; Ajinkya Mansing Pawar; Sarang Sharma (Wolters Kluwer Medknow Publications, 2021)
Mucosal fenestration is a clinical condition wherein the root apex of an affected tooth is visible in the oral cavity due to loss of overlying alveolar bone and mucosa, while dehiscence results in denudation of the root surface due to loss of overlying alveolar bone including the marginal bone. A 25-year-old male patient reported with primary concern of defect in gums and discoloration in an upper central incisor. Examination revealed an intricate case of combined mucosal fenestration and dehiscence occurring concomitantly with an endodontic lesion in an open apex anterior tooth. Cone-beam computed tomographic scan, in addition to routine diagnostic aids, supplemented the diagnosis and facilitated meticulous treatment planning. Both conventional and surgical endodontic procedures were carried out. This was followed by periodontal plastic surgery and prosthodontic rehabilitation of the discolored tooth. Complete healing of soft tissue defect was seen in 6 months, while complete bony healing was seen at 12 months. The treatment thus aimed at correcting the pathology, handling the psychological concerns, and restoring physiologic function and aesthetics by reconstruction of the lost periodontium around the involved tooth.